Information seeking behavior of academicians at Malaysia Institute of Integrative Media (MIIM), Taman Setiawangsa, Kuala Lumpur / Mohd Rafiz Salji - Salji, Mohd Rafiz (2009)
This research investigated the information seeking behavior of academicians with regard to fulfill their needs in teaching and learning methods. The survey was carried out at Malaysia Institute of Integrative Media (MIIM), Setiawangsa, Kuala Lumpur. In this case study, the methodology that had been used is questionnaire which supported relevant data to collect from those academicians that been chosen as sample at earlier stage. Among the findings of the study are majority of academicians agreed the training skills in information searching is important to the academicians, Internet becomes preferred information resource among them, they chosen information resource that obtained information which easier and quicker accessed, Librarians become preferred person in helping search information in the library, system failure is common faced by the academicians in searching information and library resources becomes valuable to them.